Infraestructura tecnológica para mejorar la seguridad de red y eficiencia operativa en la Empresa Fumiground S.A.S. - Aguayo Saa, Adonis David (2025)
The advancement of information technologies has driven the need for secure and efficient technological infrastructures in the business environment. The objective of this research is to design the technological infrastructure for the company Fumiground S.A.S. in order to improve security and operational efficiency. A quantitative approach methodology of correlational level with a non-experimental design is used, using instruments such as surveys to analyze them and propose improvement solutions. The results show that an adequate technological infrastructure with intelligent network solutions strengthens network security, positively impacting productivity and operational efficiency, which are key to business, continuity and competitiveness.